Cycloaddition versus Alkylation Reactions of 2‐Vinylindoles with α, β‐Unsaturated Carbonyl Compounds Under Gold Catalysis. Issue 28 (6th August 2013) - Pirovano, Valentina; Dell'Acqua, Monica; Facoetti, Diego; Nava, Donatella; Rizzato, Silvia; Abbiati, Giorgio; Rossi, Elisabetta
Abstract: The gold‐catalyzed intermolecular Diels–Alder cycloaddition and competitive Michael addition reactions between 2‐vinylindoles and enones/enals are reported. The reaction outcome strictly correlates with the electronic character of the heteroaromatic substrate. Thus, Diels–Alder cycloadducts are the sole products in the presence of less electron‐rich heterocycles, whereas Michael addition adducts are observed with more electron‐rich heterocycles. Plausible competitive reaction mechanisms are proposed and discussed as well. Abstract : The Diels–Alder (DA) cycloaddition and competitive Michael addition (MA) reactions between 2‐vinylindoles and α, β‐unsaturated carbonyl compounds under cationic gold(I), gold(III), and boron trifluoride catalysis are described.